Visions profanes du futur de la mobilité spatiale - Alexandre Rigal (Temporalités)
For the founding fathers of the social sciences, the future was key. Marx, Tarde, Durkheim, Weber address the question of Progress and long-term change in society. Their work put an end to the monopoly of metaphysics on the future and opened the door to the first scientific inquiries into the theme.Today, it is possible to use the methods of the social sciences to renew our visions of the future, focusing on explorations by non-experts. To this end, what better theme than space mobility to explore the future? Mobility is a daily activity and a symbol of progress, thanks to the technical innovations that have furthered its development over the past two centuries. In order to examine lay visions of the future under the angle of spatial mobility, 53 qualitative interviews were conducted. The results obtained make it possible to understand the visions of the future of mobility and the evolution of the forms of time that inhabit contemporary individuals, whether they are progressive, fatalistic, or rhizomatic. These visions concern global warming, the end of oil and the end of the automobile. Through non-expert visions, the inquiry thus covers the most salient issues of contemporary societies.